Using nirmatrelvir/ritonavir in patients with epilepsy: An update from the Israeli chapter of the International League Against Epilepsy. Issue 5 (9th March 2022) - Noyman, Iris; Ekstein, Dana; Fahoum, Firas; Herskovitz, Moshe; Linder, Ilan; Ben Zeev, Bruria; Eyal, Sara
Abstract: Presented herein are recommendations for use of nirmatrelvir/ritonavir in patients with epilepsy, as issued by the Steering Committee of the Israeli chapter of the International League Against Epilepsy. The recommendations suggest that patients on moderate‐to‐strong enzyme‐inducing antiseizure medications (ASMs) and everolimus should not be treated with nirmatrelvir/ritonavir; rectal diazepam may be used as an alternative to buccal midazolam; doses of ASMs that are cytochrome P450 (CYP3A4) substrates might be adjusted; and patients treated with combinations of nirmatrelvir/ritonavir and ASMs that are CYP3A4 substrates or lamotrigine should be monitored for drug efficacy and adverse drug reactions.